GABAergic Circuit Dysfunctions in Neurodevelopmental Disorders - Chattopadhyaya, Bidisha; Di Cristo, Graziella (Frontiers in Psychiatry, 2012)
GABAergic interneurons control neuronal excitability, integration, and plasticity. Further, they regulate the generation of temporal synchrony and oscillatory behavior among networks of pyramidal neurons. Such oscillations within and across neural systems are believed to serve various complex functions, such as perception, movement initiation, and memory. Alterations in the development of GABAergic circuits have been implicated in various brain diseases with neurodevelopmental origin. Here, we highlight recent studies suggesting a role for alterations of GABA transmission in the pathophysiology of two neurodevelopmental diseases, schizophrenia and autism. We further discuss how manipulations of GABA signaling may be used for novel therapeutic interventions.